Influenza vaccination rates in children: a multicenter nationwide study - Yakın, Hacer; Aykaç, Kübra; İçöz, Sultan; Kolukırık, Halit; Gerçek, Gülce; Arslan, Ece; Demir, Osman Oğuz; Güdeloğlu Çetiz, Elif; Sinanoğlu, Muhammed Selçuk; Kaçar, Pelin; Gülderen, Mustafa; Özer, Arife; et al. (The Turkish Journal of Pediatrics, 2026)
Background. Influenza remains a major cause of morbidity and mortality in children worldwide, yet vaccination coverage is still suboptimal in many countries. We aimed to understand parental awareness, attitudes, and determinants of vaccine uptake to guide effective strategies for increasing coverage and protecting vulnerable pediatric populations.Method. A cross-sectional study was conducted between October 2023 and May 2024 in 38 hospitals across 23 provinces in Türkiye. Data were collected from 5002 families through face-to-face interviews, with 4404 valid responses analyzed.Results. The overall influenza vaccination rate among children was 4.4% (n=195/4404). Vaccination coverage was slightly higher in high-risk groups compared to non-high-risk groups (5.2% vs. 3.5%, p=0.003). Factors positively associated with vaccination uptake included the presence of chronic illness in the child (15.1% in vaccinated vs. 4.7% in unvaccinated, p
Keywords: children; influenza; vaccination